Biomolecules Responsible for the Total Antioxidant Capacity (TAC) of Human Plasma in Healthy and Cardiopathic Individuals: A Chemical Speciation Model - Enrico Prenesti; Silvia Berto; Fabio Gosmaro; Marco Bagnati; Giorgio Bellomo (MDPI AG, 2021)
(1) Background: Much effort has been expended to investigate the antioxidant capacity of human plasma, attempting to clarify the roles of both metabolic and food substances in determining defenses against oxidative stress. The relationship between the total antioxidant capacity (TAC) and the concentrations of redox-active biomolecules in the human plasma of healthy and cardiopathic individuals was investigated in the present study to develop a chemical speciation model. (2) Methods: Plasma was collected from 85 blood donors and from 25 cardiovascular surgery patients. The TAC was measured using the CUPRAC-BCS (CUPric Reducing Antioxidant Capacity - Bathocuproinedisulfonic acid) method. Biomolecule concentrations were determined via visible spectrophotometry or HPLC/RP techniques. The relationship between the TAC and the concentrations was defined by applying a multiple regression analysis. The significance of the variables was first tested, and chemical models were proposed for the two datasets. The model equation is β<semantics>TAC=<mstyle displaystyle="true" mathsize="70%">∑</mstyle>iβi·<mfenced close="]" open="[">Ai</mfenced></semantics>, where βi and [Ai] are the electronic exchange and the molar concentrations of the ith antioxidant component, respectively. (3) Results: The major contributions to the TAC, ~80%, come from endogenous compounds in both healthy and cardiopathic individuals, whereas the contributions from exogenous compounds were different between the two datasets. In particular, γ-tocopherol showed a different role in the chemical models developed for the two groups.